2019
DOI: 10.3390/molecules24234329
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics Versus Natural Biomolecules: The Case of In Vitro Induced Bacteriospermia by Enterococcus Faecalis in Rabbit Semen

Abstract: Male subfertility is a global issue in human reproduction as well as in animal reproduction. Bacterial infection and semen contamination are still widely overlooked. As the collection of ejaculates is not a sterile process, it is necessary to add antimicrobial agents to avoid a possible depreciation of semen samples. As traditionally used antibiotics have been questioned because of an ever-increasing bacterial resistance, natural bioactive molecules could offer an alternative because of their antibacterial and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(72 citation statements)
references
References 93 publications
3
68
0
1
Order By: Relevance
“…A modern trend in the development of new semen extenders is the application of alternative supplements that could contribute to the reduction of sperm damage resulting from ex vivo semen processing. A systematic screening of natural resources also represents a continual effort by the scientific community to discover new substances with the potential to replace antibiotics in animal production [ 51 , 52 ]. Based on a convincing evidence that the biomolecules present in Schisandra possess antibacterial properties, we studied the efficiency of the Omija extract to inhibit the growth of common pathogens ( K. pneumoniae , S. sonei , and L. monocytogenes ), as well as bacteria previously detected in semen samples collected from rabbits, bulls, and boars ( B. cereus , E. faecalis , and P. aeruginosa ) [ 52 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A modern trend in the development of new semen extenders is the application of alternative supplements that could contribute to the reduction of sperm damage resulting from ex vivo semen processing. A systematic screening of natural resources also represents a continual effort by the scientific community to discover new substances with the potential to replace antibiotics in animal production [ 51 , 52 ]. Based on a convincing evidence that the biomolecules present in Schisandra possess antibacterial properties, we studied the efficiency of the Omija extract to inhibit the growth of common pathogens ( K. pneumoniae , S. sonei , and L. monocytogenes ), as well as bacteria previously detected in semen samples collected from rabbits, bulls, and boars ( B. cereus , E. faecalis , and P. aeruginosa ) [ 52 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Again, the collected data suggesting that the extract is more effective against Gram-positive bacteria complement the previous findings published by Hussain et al [ 56 ], Teng and Lee [ 57 ], and Mocan [ 36 ], hypothesizing that Gram-positive bacteria are more sensitive to plant essential oils than Gram-negative bacteria. It has been previously reported that bioactive compounds present in plant products such as resveratrol or quercetin have the ability to provide protection to animal spermatozoa against deleterious changes to their structure and function as a result of bacterial contamination [ 52 ]. Therefore, S. chinensis could become an interesting source of alternative supplements to semen extenders providing higher protection of male gametes against bacteriospermia.…”
Section: Resultsmentioning
confidence: 99%
“…Even though semen collection protocols in the livestock industry are very strict, semen collection is not a sterile process, and the addition of antibiotics to extenders to control contaminating bacterial populations is a routine fact at farm level. The efficacy of different antibiotics added to semen extenders in livestock has been widely demonstrated [ 44 ]. However, how quickly bacteria acquire tolerance and/or resistance to antibiotics is essential.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study demonstrated that sperm microbiota diversity is influenced by host genetics [ 9 ]. The rabbit semen samples were contaminated with bacteria, especially those that belong to the Enterobacteriaceae family [ 44 ], ranging from 27.6% for Line V to 50.9% for Line R of semen samples analysed [ 9 ]. Bacteria contamination, such as Enterobacteriaceae family might adversely affect the quality of semen used for AI [ 4 ] and is an important hygiene indicator [ 5 ], although the majority of these bacterial strains are not currently considered pathogens [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cells from the 1 mL fresh overnight culture were used for the ethanol-formic acid extraction, covered with 1 µL of matrix solution (saturated solution of α-cyano-4-hydroxycinnamic acid in 50% acetonitrile with 2.5% trifluoroacetic acid; Bruker Daltonics), and subsequently dried in air for 15 min. Protein spectrum of the sample was generated by the Biotyper software, version 3.0 (Bruker Daltonics) and analyzed as previously described [ 58 ].…”
Section: Methodsmentioning
confidence: 99%